МАКСИМІЗАЦІЯ ДІАПАЗОНУ КЕРУВАННЯ МАТРИЧНИМИ ПЕРЕТВОРЮВАЧАМИ - Михальський, В.М.; Соболєв, В.М.; Чопик, В.В.; Шаповал, І.А. (Інститут електродинаміки НАН України, Київ, 2015)
The features of the matrix converter control to achieve the maximum volume of the surface, which is limited by the maximum values of the voltage transfer ratio in coordinates of the phase shift between voltage and current on the input and output have been considered. The analysis is realized based on a vector representation of all discrete values of the mathematical model of the converter. An appropriate modulation strategy and an algorithm for direct control of a set of voltage transfer ratio and the transfer ratio of the reactive component of the input current as a function of output power factor by direct assignment of the required parameters of the duty-cycle space vectors has been proposed. The simulation results are presented. References 7, table 1, figures 5.